India's water economy - Briscoe, John; Malik, R.P.S. (New Delhi, 2006)
This report argues that India faces a turbulent future in water resources. It examines the evolution of the management of India's waters, describes the achievements of the past, and analyses the looming set of challenges. Drawing heavily on background documents by eminent Indian practitioners and policy analysts, the study suggests what changes should be considered and how to manage the transition from 'the ways of the past' to 'the ways fo the future' in a principled and pragmatic manner
Keywords: Water-Economic aspects